Hydrogen Accumulation and Distribution in Zr1Nb Zirconium Alloy after Electrochemical and Gas-Phase Hydrogenation; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kudiyarov V. N. Victor Nikolaevich (2016, 2016)
Title screen